Performance of RoFSO OFDM System under Malaysia Climatic Condition for Wireless Communication - Hidayah M. Yusri; Irneza Ismail; Wan Zakiah Wan Ismail; Mus'ab Sahrim; Khairul Nabilah Zainul Arifin; Sharma Rao Balakrishnan; Juliza Jamaludin (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceeding Kolokium Siswazah Fakulti Sains Dan Teknologi 2020 (KOSIST 2020) “Synergizing Innovation and Research Through Science and Technology” 9th December 2020 Organized by Faculty Science and Technology